Rotational viscosity of induced smectic C* phase of liquid crystal - Popova, E.V.; Fedoryako, A.P.; Vashchenko, V.V.; Kutulya, L.A. (Functional Materials, 2007)
The rotation viscosity and the molecular tilt angle 0 have been determined in smectic layers of induced ferroelectric liquid crystal system containing some 1R, 4R-2-(4-phenyl-benzylidene)-p-menthane-3-one derivatives as chiral dopants. The correlation between the rotational viscosity and the angle 0 has been studied. The temperature dependence of the smectic tilt angle.